PSYCHOLOGICAL FEATURES OF PERSONAL RELATIONSHIPS IN PRIMARY SCHOOL AGE STUDENTS - DILOROM ANVAROVNA, KHOSHIMOVA (European Journal of Life Safety and Stability (2660-9630), 2021)
Interpersonal relationships of younger schoolchildren are characterized primarily by the narrowness of interpersonal ties. Most often, this is a relationship between two children; groups either do not arise at all, or appear sporadically. There are practically no mutual preferences between boys and girls. As a result, the structure of interpersonal relationships turns out to be very amorphous, consisting of two emerging substructures - boys and girls. Leadership here is of a single and expanded nature, and each of the substructures has its own leaders. Researchers of this problem agree that younger schoolchildren have an emotional attitude to their comrades.